Intersex, Theology, and the Bible
X, 241 p.
Keywords: Intersex bodies have been figured as troubling by doctors, parents, religious institutions and society at large. In this book, scholars draw on constructive and pastoral theologies, biblical studies, and sociology, suggesting intersex's capacity to 'trouble' is positive, challenging unquestioned norms and assumptions in religion and beyond.